Influence of Environmental Factors on Embryonic Development and Fetal Programming in South Africa - Lubanzi, Michael (International Journal of Biology, 2024)
Purpose: The aim of the study was to investigate the influence of environmental factors on embryonic development and fetal programming Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed compelling evidence linking various environmental exposures, including air pollution, maternal nutrition, smoking, stress, chemical contaminants, and heavy metals, to adverse pregnancy outcomes and long-term health consequences for offspring. The study also highlighted the critical role of epigenetic modifications, such as DNA methylation, histone modifications, and non-coding RNA expression, in mediating the effects of environmental factors on gene expression and cellular function during embryogenesis. Unique Contribution to Theory, Practice and Policy: Developmental Origins of Health and Disease (DOHaD) theory & Fetal Programming theory may be used to anchor future studies on the influence of environmental factors on embryonic development and fetal programming. Incorporate comprehensive assessments of environmental exposures into routine prenatal care. Healthcare providers should consider factors such as maternal diet, smoking status, stress levels, chemical exposures, and air quality when counseling pregnant individuals. Advocate for stricter environmental regulations aimed at reducing exposure to air pollutants, endocrine-disrupting chemicals, heavy metals, and other harmful substances during pregnancy. Tailor interventions based on individual risk profiles and environmental exposures. For example, provide targeted nutritional counseling, smoking cessation programs, stress management support, and referrals for environmental health assessments as part of prenatal care services.